A preliminary study on a novel bioaugmentation technique enhancing lactic acid production by mixed cultures fermentation. (November 2021) - Policastro, Grazia; Carraturo, Federica; Compagnone, Mariacristina; Giugliano, Marco; Guida, Marco; Luongo, Vincenzo; Napolitano, Raffaele; Fabbricino, Massimiliano
Graphical abstract: Highlights: A bioaugmentation technique to select cultures producing lactic acid is proposed. The selection occurs via sequential batch steps with intermittent pH correction. Substrate concentration affects the efficacy of the bioaugmentation technique. As consequence of the bioaugmentation, lactic acid increases from 5% to 59% The technique results in microbial population change to Bacillus species. Abstract: The paper is a preliminary study on the selection of lactic acid producing microorganisms from a mixed microbial population via bioaugmentation. The bioaugmentation technique is based on pH sudden variations occurring in sequential batch steps of a dark fermentation process applied to simple substrates. Different conditions are tested and compared. The structure of microbial communities and concentrations of metabolic intermediates are analyzed to study the possible substrate conversion routes. Obtained results indicate that the initial mixed culture produced a lactic acid percentage of 5% in terms of CODLA /CODPRODUCTS . In the most favourable conditions, the selected culture produced a lactic acid percentage of 59%. The analysis of the composition of microbial communities before and after the bioaugmentation processes, indicates that lactic acid production mainly results from the population change to bacteria belonging to the genus Bacillus. Indeed, the relative abundance of Bacilli increased from 0.67%, to 8.40% during the bioaugmentation cycle.